Analisis Pengaruh Kecukupan Modal, Risiko Pasar dan Efisiensi Operasional terhadap Risiko Kredit Perbankan - Luh Nadi (Ma'soem University, 2021)
This study aims to examine The Effect Of Capital Adequacy, Market Risk, And Operational Efficiency On Bank Credit Risk. The Research Sample is 10 Conventional Commercial Banks Listed On The Indonesia Stock Exchange. The research variables were proxied by CAR, NIM, and BOPO for the independent variable and NPL for the dependent variable. This study uses quantitative data sourced from banking financial reports on the website of the financial services authority (OJK). The analysis technique uses panel data regression and testing using the software program Eviews (econometric Views) version 9. The results show that capital adequacy proxied by CAR and Operational Efficiency Proxied by BOPO have a significant positive effect on the variable risk of credit or non performing loan proxied by NPL, while market risk proxied by NIM has no effect on NPL.